2013
DOI: 10.3109/02713683.2013.836542
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles in Tears Accompanying the Secondary Conjunctival Responses Induced by Nasal Allergy

Abstract: Different cytokine profiles in the tears accompanying the immediate, late and delayed types of SCR, induced by nasal allergy, would indicate involvement of different hypersensitivity mechanisms in the particular SCR types. The low cytokine concentrations in tears recorded during the SCRs may suggest their origin from the nasal mucosa. These results emphasize the diagnostic value of NPTs with allergens combined with monitoring of various ocular features in patients suffering from the secondary form of AC. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…As most groups did not examine the amount of G-CSF in AR, little is known about its impact on AR. Pelikan [ 34 ] found elevated levels in tears of SAR patients after allergen provocation, providing evidence for an influence of G-CSF in this disease entity. But further research is needed to define its role in allergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As most groups did not examine the amount of G-CSF in AR, little is known about its impact on AR. Pelikan [ 34 ] found elevated levels in tears of SAR patients after allergen provocation, providing evidence for an influence of G-CSF in this disease entity. But further research is needed to define its role in allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Data on these two general markers of inflammation in nasal fluids are inconsistent [ 12 ]. Pelikan [ 34 ] did not find elevated levels of IL-6 in tears of allergic subjects. This is consistent with our results, but disagrees with an elevation of IL-1β and IL-6 found by others [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 levels were higher in nasal biopsy specimens from patients with persistent AR vs. controls (114). Pelikan demonstrated high concentrations of IL-8 in tears from patients with AR after nasal provocation tests with allergen (115,116). In conclusion, IL-8 is a key player in the pathogenesis of asthma through its roles in neutrophil functions.…”
Section: Chemokines Associated With Function Of Th1 Lymphocytesmentioning
confidence: 81%
“…The activation of mast cells in a Th2 microenvironment is a critical characteristic in allergic conjunctivitis inflammation [35]. At the ocular surface level, IL-10 is produced by conjunctival fibroblasts [36], by blood inflammatory cells such as basophils and eosinophils, and by local mast cells after an allergenic challenge [37,38]. Some authors have suggested a pathogenic role of IL-10 in ocular surface inflammatory diseases in which the Th2 profile is associated with ocular damage [39,40], and in a mice model of induced allergic conjunctivitis, IL-10 contributed to the development of the acute effector phase, augmenting the infiltration of eosinophils into the conjunctiva [41].…”
Section: Discussionmentioning
confidence: 99%